Optimasi Gerakan Operator Dengan Time and Motion Study untuk Efisiensi Produksi - Syafruddin Dwi Saefi Ismail; Anita Oktaviana Trisna Devi; Bekti Nugrahadi (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The garment industry, as a labor-intensive sector, faces challenges related to efficiency and production cost due to the large number of operator movements that do not add value. As a garment manufacturing company, PT Fashion Stitch Joshua experiences this problem in the form of increased cycle time causes by many non value added operator motion. This study aims to design standardized motion to improve efficiency. The method used is a time and motion study through therbligh analysis to identify, classify, and eliminate ineffective movement. Data were collected through direct observation, video documentation, and cycle time measurement. The result show that the high cycle time in the join side seam process is caused by the large proportion of ineffective motion in the operators work methods. Therbligh analysis indicates that non value added motion elements significantly contribute to reduced efficiency, thereby confirming the hypothesis regarding the importance of improving work methods. Through the redesign of motion based on therbligh principles, the cycle time was reduced from 39.09 second to 29,50 second, representing an efficiency improvement of 24%. The implementation of standardized motion design is proven to be more effective in improving efficiency and can serve as a reference for production processes in the garment industry.